2019
DOI: 10.1523/jneurosci.2626-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

ICAM5 as a Novel Target for Treating Cognitive Impairment in Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is the most common inherited form of intellectual disability, resulted from the silencing of the Fmr1 gene and the subsequent loss of fragile X mental retardation protein (FMRP). Spine dysgenesis and cognitive impairment have been extensively characterized in FXS; however, the underlying mechanism remains poorly understood. As an important regulator of spine maturation, intercellular adhesion molecule 5 (ICAM5) mRNA may be one of the targets of FMRP and involved in cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…Concomitant to an overabundance of thin and branched spines, we detected a decreased abundance of mushroom spines that also displayed smaller heads than WT, a finding in agreement with reports by others [ 46 , 47 , 51 ]. Mushroom spines form strong synapses, as indicated by the correlation of head dimensions with higher synaptic strength and AMPA receptor content [ 81 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Concomitant to an overabundance of thin and branched spines, we detected a decreased abundance of mushroom spines that also displayed smaller heads than WT, a finding in agreement with reports by others [ 46 , 47 , 51 ]. Mushroom spines form strong synapses, as indicated by the correlation of head dimensions with higher synaptic strength and AMPA receptor content [ 81 ].…”
Section: Discussionsupporting
confidence: 93%
“…Early studies in FXS patients indicated an overabundance of spines [ 44 ], however, analysis of Fmr1 KO mice has produced conflicting results, in particular in the hippocampal region [ 45 ]. In the mature (>60 PND) hippocampus of Fmr1 KO mice, either an increased density of dendritic protrusions [ 46 , 47 ], normal density [ 48 ], or subregion-specific differences were noted compared to WT [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…[64][65][66][67]. For example, a subset of FMRP target genes including Icam5 (intercellular adhesion molecule 5) [68], Gsk3β (glycogen synthase kinase 3 beta) [50] and glutamate receptor subunits [69] have shown increased protein levels in Fmr1 KO mice. In the present study, however, protein levels of Nf1, Ctnnb1, and mTOR were normal in the Fmr1 KO neocortex, which is similar to previous results regarding other FMRP target genes such as Psd-95 (also known as Dlg4, discs large MAGUK scaffold protein 4) [70], Snap25 (synaptosome associated protein 25) [71] and Cyfip1(cytoplasmic FMR1 interacting protein) [72].…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular adhesion molecule 5 (Icam5) and neuroligin-1 (Nlgn1) are cell adhesion molecules linked to neuropsychiatric disorders, including autism, and they play important roles in synapse development and function. [35][36][37] The neuronal pentraxin receptor (Nptxr) is involved in synapse organization and is a potential biomarker of Alzheimer's disease progression. 38,39 Plexin-A4, Nlgn1, Icam5, and Nptxr were independently validated by ELISA, and all showed robust and specific binding to CS-E-, but not CS-C-enriched, polysaccharides ( Figure 4F).…”
mentioning
confidence: 99%
“…Our findings suggest a new potential role for CS-E in the regulation of Sema3A/plexin-A4 complexes and semaphorin signaling. Intercellular adhesion molecule 5 (Icam5) and neuroligin-1 (Nlgn1) are cell adhesion molecules linked to neuropsychiatric disorders, including autism, and they play important roles in synapse development and function. The neuronal pentraxin receptor (Nptxr) is involved in synapse organization and is a potential biomarker of Alzheimer’s disease progression. , Plexin-A4, Nlgn1, Icam5, and Nptxr were independently validated by ELISA, and all showed robust and specific binding to CS-E-, but not CS-C-enriched, polysaccharides (Figure F). Together, these results demonstrate the ability of our GAG photo-cross-linking probes to selectively capture and identify novel GAG-BPs.…”
mentioning
confidence: 99%